Sāhityāvalōkaṃ : nirūpaṇaṃ - Parameswaran Pillai, Erumeli, 1931- (Jayanthi Publishers ; vitariaṇaṃ, Dēśābhimāni Bukk Haus, 1979)
Articles in appreciation of some Malayalam works by Marxist writers from Kerala.